Effect of the 2015 Code Revision to the Corporate Governance Code on Japanese Listed Firms - Yanagida, Tomotaka (Asian Academy of Management Journal of Accounting and Finance, 2022)
The Corporate Governance Code, revised in 2015, recommends that the firms listed within the first and second sections of Japan’s Tokyo Stock Exchange select two or more independent outside directors (Corporate Governance Code 4-8). Japanese listed firms must either comply with or explain the reason for non-compliance. This study investigates how the Corporate Governance Code affects Japanese listed firms. Using a difference-in-differences approach for our sample of 4,200 firm–year observations in 2014–2015, we find that the Corporate Governance Code increases the proportion of outside directors by approximately 8.8%. This finding implies that such companies might have found it difficult to explain non-compliance with this rule to their shareholders. Moreover, we find no evidence that increases in the ratio of outside directors are related to a firm’s future performance.